2015
DOI: 10.1016/j.antiviral.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The Herpes Simplex Virus-1 genome contains multiple clusters of repeated G-quadruplex: Implications for the antiviral activity of a G-quadruplex ligand

Abstract: Guanine-rich nucleic acids can fold into G-quadruplexes, secondary structures implicated in important regulatory functions at the genomic level in humans, prokaryotes and viruses. The remarkably high guanine content of the Herpes Simplex Virus-1 (HSV-1) genome prompted us to investigate both the presence of G-quadruplex forming sequences in the viral genome and the possibility to target them with G-quadruplex ligands to obtain anti-HSV-1 effects with a novel mechanism of action. Using biophysical, molecular bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
164
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 51 publications
10
164
0
Order By: Relevance
“…We have previously shown that at least four G-rich repeated sequences in the HSV-1 genome can fold into G4 structures in vitro (17). Three sequences feature four GGGG-tracts, while one sequence has four GGG-tracts, displaying the ability to form multiple monomolecular 4- or 3-tetrad stacked G4, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that at least four G-rich repeated sequences in the HSV-1 genome can fold into G4 structures in vitro (17). Three sequences feature four GGGG-tracts, while one sequence has four GGG-tracts, displaying the ability to form multiple monomolecular 4- or 3-tetrad stacked G4, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The herpes simplex virus-1 (HSV-1) genome has a very high GC content (68%) which peaks at 84.7% GC in simple sequence repeats (SSRs) (16). Recently we provided evidence for the presence of very stable G4-forming regions located in the HSV-1 inverted repeats (17). In particular, multiple conserved and extended clusters of G4 forming sequences were observed, covering about 2,000 bp of the 152,000 bp-viral genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Artusi et al, have reported the presence of G-quadruplex repeats in the HHV-1 genome [17]. It is well known that G-quadruplex structures are very stable.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on G-quadruplexes in virus genomes are limited. A few studies show functional roles of selected RNA or DNA G-quadruplex motifs present in the virus genome in vitro [1317] or describe the genomic location of G-quadruplexes in virus genomes [18]. …”
Section: Introductionmentioning
confidence: 99%